2019
DOI: 10.1007/978-3-030-16722-6_14
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Nominal Cross-Language Clone Detection

Abstract: In this paper we address the challenge of cross-language clone detection. Due to the rise of cross-language libraries and applications (e.g., apps written for both Android and iPhone), it has become common for code fragments in one language to be ported over into another language in an extension of the usual "copy and paste" coding methodology. As with single-language clones, it is important to be able to detect these cross-language clones. However there are many real-world crosslanguage clones that existing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
7
0
3
Order By: Relevance
“…Prior work has shown that identifiers impact source code comprehension, especially for beginners [14], and as developers must understand the code returned by search, tokens are an important consideration. Prior work in code-to-code search that relies on ASTs have seen high precision and recall [43,63] suggesting that is an important consideration as well. Individually, each measure has shortcomings.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work has shown that identifiers impact source code comprehension, especially for beginners [14], and as developers must understand the code returned by search, tokens are an important consideration. Prior work in code-to-code search that relies on ASTs have seen high precision and recall [43,63] suggesting that is an important consideration as well. Individually, each measure has shortcomings.…”
Section: Motivationmentioning
confidence: 99%
“…Techniques that use static code attributes to compute similarity often parse code into an intermediate representation based on text [7,36,47], AST [11,34] or graph-based [26,46] and compute a measure for syntactic similarity. For cross-language syntactic similarity, most techniques are text-based [43,56,58]. Tree-and graph-based approaches have not been explored for cross-language similarity due to language specific grammar.…”
Section: Code Similaritymentioning
confidence: 99%
“…Several recent studies have reported on cross-language code clone detection [58,88,59]. For example, LICCA, a tool for cross-language clone detection [82] is based on a tree-based intermediate representation of the source code.…”
Section: Extensibility Of Experiments Testbed For Software Engineering Experimentsmentioning
confidence: 99%
“…e main idea of these approaches is to convert the source code written in different languages into common tree structures, such as eCST (enriched concrete syntax tree) [5], AST [27,28], and CodeDOM (Code Document Object Model) [29]. en, the tree structures are converted into token sequences or vectors to improve the efficiency of similarity measure.…”
Section: Cross-language Source Code Similarity Detection Through Tree-based Intermediate Representationmentioning
confidence: 99%